2020
DOI: 10.1039/c9ay02582k
|View full text |Cite|
|
Sign up to set email alerts
|

Identification, isolation, structural characterisation, synthesis and in silico toxicity prediction of the alkaline hydrolytic degradation product of brivaracetam by using LC-PDA, preparative HPLC, LC/HESI/LTQ, FTIR, and 1H NMR

Abstract: Brivaracetam is a racetam derivative of levetiracetam with very limited data available on its degradation behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The data were used to build the model through physical–chemical descriptors and Mondrian’s shaped prediction, which offers similar prediction accuracy for both active and inactive sets, where the validity values are around 0.90, at a significance level of 0.1. This toxicological web server predicts the molecular toxicity of the target molecule based on the mechanism of action in different animal models and their organs [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data were used to build the model through physical–chemical descriptors and Mondrian’s shaped prediction, which offers similar prediction accuracy for both active and inactive sets, where the validity values are around 0.90, at a significance level of 0.1. This toxicological web server predicts the molecular toxicity of the target molecule based on the mechanism of action in different animal models and their organs [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…BRV in bulk and its dose forms may now be accurately measured via a simple reverse-phase liquid chromatographic method devised by Salomi et al, (23). To separate the samples, a C18 column was used, with a flow rate of 1.2 ml/min of methanol: buffer as the mobile phase.…”
Section: Results Pharmaceutical Methods Of Brvmentioning
confidence: 99%
“…It is relatively unknown what the alkaline hydrolytic degradation product of BRV consists of. Rupal Dubey et al (27) published a research paper that identified this product, isolated it, characterized it structurally, and predicted its in-silico toxicology. An isocratic reverse-phase HPLC-UV technique was developed to determine BRV in the presence of impurities and degradation products.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…Stability indicating assay methods is useful to study the possible degradation pathway of drug substance and drug products. Forced degradation studies are recommended to study the degradation pathway and knowledge of degrading products of drug substance and their products [25][26][27][28][29] .…”
Section: Regulatory Requirement Of Stability Indicating Methods Develomentioning
confidence: 99%